Marketing Public Relations Metropolitan City Pekanbaru Menjaga Mitra Bisnis - Tantri Puspita Yazid (Communiverse : Jurnal Ilmu Komunikasi, 2022)
This study aims to determine the strategy Marketing Public Relations of Metropolitan City Pekanbaru and the driving factors in do business partners. This research uses qualitative research methods. The subjects in this study used purposive techniques. The results of this study indicate that the strategy carried out by the Marketing Public Relations Metropolitan City Pekanbaru, namely through the concept of Marketing Public Relations with Pull strategi, by showing promo rental prices, conduct events, other strategies used is "Pick the Ball" by showing good visit or traffic owned Metropolitan City Pekanbaru. Push strategy, the reason business partners choose Metropolitan City Pekanbaru because of the communication that is maintained by Marketing Public Relations with business partners, the help of business partners on rental price discount imposed by management during the Covid-19 period, completeness of facilities owned by Metropolitan City Pekanbaru. Pass strategy, help promote products through social media instagram @mtc-panam, discount the rental prices of Covid-19 pandemic, maintain relationships by providing advice boxes for business users and provide clear terms and conditionss. The results of this study can be a reference material for Metropolitan City Pekanbaru, which in order to maximize in maintaining relationships with business stakeholders where it would be better if Metropolitan City Pekanbaru is more active in helping promote the tenant by actively presenting the news of the existence of tenants modren and traditional concepts so that the wider audience can be more familiar with Metropolitan City Pekanbaru